2020
DOI: 10.1101/2020.06.19.154930
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 growth, furin-cleavage-site adaptation and neutralization using serum from acutely infected, hospitalized COVID-19 patients

Abstract: SARS-CoV-2, the causative agent of COVID-19, emerged at the end of 2019 and by mid-June 2020, the virus has spread to at least 215 countries, caused more than 8,000,000 confirmed infections and over 450,000 deaths, and overwhelmed healthcare systems worldwide. Like SARS-CoV, which emerged in 2002 and caused a similar disease, SARS-CoV-2 is a betacoronavirus. Both viruses use human angiotensin-converting enzyme 2 (hACE2) as a receptor to enter cells. However, the SARS-CoV-2 spike (S) glycoprotein has a novel in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 56 publications
5
51
1
Order By: Relevance
“…SARS-CoV-2 acquired a furin cleavage site not found in SARS-CoV-1 or any other known sarbecovirus. Studies have shown that acquisition of this furin cleavage site could be beneficial to the virus, because mutations at this site decrease viral infectivity [ 4 , 14 , 21 , 58 ], but in other contexts or other mutations of the furin cleavage site, infectivity is increased [ 4 , 35 , 58 , 59 ]. We currently do not know whether viruses without the furin cleavage site would replicate more efficiently in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 acquired a furin cleavage site not found in SARS-CoV-1 or any other known sarbecovirus. Studies have shown that acquisition of this furin cleavage site could be beneficial to the virus, because mutations at this site decrease viral infectivity [ 4 , 14 , 21 , 58 ], but in other contexts or other mutations of the furin cleavage site, infectivity is increased [ 4 , 35 , 58 , 59 ]. We currently do not know whether viruses without the furin cleavage site would replicate more efficiently in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…One caveat is that visualization of isogenic D614 and G614 variant SARS-CoV-2 by scanning EM and transmission EM did not reveal significant differences in spike density [ 48 ], which cannot be explained by the masking effect of contaminating S protein. Because many studies have observed deletion of the furin cleavage site in live SARS-CoV-2 in few as two to three passages in Vero cells [ [58] , [59] , [60] , [61] ], care must be taken to ensure that studies of live viruses are not impacted by artifacts of this adaptation. In line with our own observations on VLPs and MLV PVs, Turonova et al visualized live SARS-CoV-2 G614 virions by cryo-EM and observed much greater spike density than was reported in prior studies with D614 viruses [ 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…While mutations in the SARS-CoV-2 MBCS decreased airway cell infectivity, they increased infectivity on VeroE6 cells. Several groups have reported mutations or deletions in or around the SARS-CoV-2 MBCS that arise in cell culture on VeroE6 cells (Klimstra et al, 2020;Lau et al, 2020;Ogando et al, 2020), indicating that the lack of a MBCS creates a selective advantage in cell culture on VeroE6 cells. The mechanism behind this remains unknown.…”
Section: Sars-cov-2 Entry and Replication Is Dependent On Serine Protmentioning
confidence: 99%
“… 3-10 In addition, neutralizing antibodies to both viral spike and nucleocapsid proteins have been found in patients. 5 , 10 , 11 The longevity of this antibody response is also still under investigation. Preliminary work found that the half-lives of antibodies recognizing the nucleocapsid, spike protein, and receptor binding domain of the spike protein are 52, 81, and 83 days, respectively, with an estimated time to negativity of 50% of the seropositive population of 195, 532, and 260 days, respectively.…”
mentioning
confidence: 99%